CUSTOMARY LAND CONFLICTS BETWEEN DAYAK INDIGENOUS LAW AND STATE LAW IN INDONESIA - Diva Rafi Anjani; Imelda Hasibuan; Ahmad Nafhani; Aryo Subroto (Awang Long Law Review, 2026)
Indonesia’s legal system is characterized by legal pluralism, in which state law coexists with customary law (adat) practiced by indigenous communities. Despite constitutional recognition and supportive judicial decisions, conflicts over customary land persist, particularly among Dayak indigenous communities in Kalimantan. These conflicts largely arise from structural incompatibilities between state land law—centered on administrative legality, formal registration, and written evidence—and customary law, which is grounded in communal ownership, oral traditions, and social legitimacy. This article analyzes conflicts between Dayak customary law and state law in the governance of customary land from a legal anthropology perspective. It examines the operation of Dayak customary law as a living law, identifies the causes and forms of conflict with state legal regimes, and assesses the implications of these conflicts for customary land governance and legal certainty. The research employs a qualitative legal-anthropological approach. Data were collected through in-depth interviews with customary leaders, community members, and relevant stakeholders, complemented by participant observation and document analysis. The data were analyzed using descriptive and interpretative methods, drawing on the concepts of legal pluralism and semi-autonomous social fields. The findings demonstrate that Dayak customary law remains effective in regulating land control, use, and dispute resolution at the community level. However, conflicts persist due to the dominance of formal state legal mechanisms that marginalize customary authority in land administration, licensing, and development processes. Normative recognition of indigenous rights alone has proven insufficient to secure legal protection for customary land. The study argues that substantive integration of customary institutions into state land governance frameworks is essential to reduce conflict, enhance legal effectiveness, and ensure meaningful protection of indigenous land rights.